The Influence of Training and Development on Work Quality Mediated by Learning Motivation at PT. Asuransi Sahabat Artha Proteksi - Leman, Ricky; Haryono, Budi; Wahyoedi, Seogeng (ID Solutions, 2024)
This research stems from the urgent need to face the increasingly complex dynamics of the insurance industry and increasingly fierce competition, especially at PT Asuransi Sahabat Artha Proteksi (Sahabat Insurance Jakarta). The company, which has undergone several changes in ownership and identity since its establishment in 1996, currently faces the challenge of improving the quality of human resources (HR) that play a crucial role in this expertise-based industry. Although the company has implemented various initiatives such as financing certification exams, monthly incentives, and integration into performance appraisals (KPIs), it still lacks a sufficient number of experts. This study aims to understand how training and development programmes can motivate employees to improve their productivity and work quality to reach expert status. By analysing the effect of training and development on the quality of employee performance mediated by motivation, this study provides insight into the importance of motivation as a mediator pathway in the context of performance improvement in the insurance industry. The results of this study are expected to provide practical recommendations for PT Asuransi Sahabat Artha Proteksi in their efforts to improve the quality of human resources and overall company productivity. The population in this study amounted to 120 (one hundred and twenty) people and for the sample of this study amounted to 92 (Ninety-two) people. The results of this analysis show that all indicators used in this study are valid and reliable. This study uses a Structural Equation Modeling (SEM) approach based on Partial Least Square (PLS) using SmartPLS 3.3 software. This study provides evidence of a positive and significant effect.